2015
DOI: 10.1155/2015/810716
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Dislodgement of Tibial Polyethylene Insert after a High-Flex Posterior-Stabilized Total Knee Replacement

Abstract: Many pathologic entities can produce a painful total knee replacement (TKR) that may lead to potential prosthetic failure. Polyethylene insert dissociation from the tibial baseplate has been described most frequently after mobile-bearing and cruciate-retaining TKRs. However, only 3 tibial insert dislocations in primary fixed-bearing High-Flex posterior-stabilized TKRs have been reported. We present a new case of tibial insert dislocation in a High-Flex model that shares similarities and differences with the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“… 3 , 4 , 5 Such an event is very rarely seen with fixed bearing high flex posterior stabilized TKA and there are only four cases reported till now. 6 , 7 , 8 , 9 All the cases used Genesis II (Smith & Nephew, Memphis, Tennessee, USA), similar to our case.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“… 3 , 4 , 5 Such an event is very rarely seen with fixed bearing high flex posterior stabilized TKA and there are only four cases reported till now. 6 , 7 , 8 , 9 All the cases used Genesis II (Smith & Nephew, Memphis, Tennessee, USA), similar to our case.…”
Section: Discussionsupporting
confidence: 68%
“…They have also stated that repeated micro motion leads to progressive wear of the thin posterior dovetails resulting into subsequent dissociation. Astoul Bonorino et al 9 reported a case of traumatic dislodgement of the insert at 32 weeks after TKA. They have associated failure of the posterior locking mechanism to be the reason for dissociation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations